Aparecida (1986), by Carlos Mastropietro. (Revista Argentina de Musicología, 2012)
This paper studies Aparecida (1986) by the Argentine composer Carlos Mastropietro (1958) in relation to the aesthetic trends that articulated the Argentine contemporary music scene during the first half of the 20th century and to the critical revision that emerged from the Latin American Center of High Musical Studies (1962-1970) at the Instituto Di Tella.Then we examine, on the one hand, his aesthetic and technical ideas around the ‘nondomestication’ of music and structural ‘fragility’, and, on the other, the function of his ‘bad memory’ that precludes textual and stylistic quotes. Finally, we analyze the piece structurally in order to characterize the resources used and to link them to his aesthetic assumptions.
Keywords: Argentine contemporary music; Carlos Mastropietro; aesthetics of music